KOMPETENSI GURU DAN DISIPLIN KERJA DALAM MEMPENGARUHI KINERJA GURU PADA MA IBRAHIMY WALI SONGO SITUBONDO DENGAN MEDIASI VARIABEL MOTIVASI KERJA - Fathorrasi, Fathorrasi; Arief, Mohammad Yahya; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2023)
Educational institutions are one of the most important elements for the progress of the nation's civilization, for that Madrasah Aliyah (MA) has an important role to be able to produce superior Indonesian human resources, Madrasah Aliyah graduates must become competitive and superior human resources. The purpose of this study was to analyze and test teacher competence and work discipline in influencing teacher performance at MA Ibrahimy Wali Songo Situbondo with mediation of work motivation variables. The population in this study was MA Ibrahimy Wali Songo Situbondo teachers. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the smart PLS 3.0 application, show that teacher competence has a significant effect on work motivation, work discipline has no significant effect on work motivation, teacher competence has a significant effect on teacher performance, work discipline has no significant effect on teacher performance, work motivation has a significant effect on teacher performance. The results of the indirect effect hypothesis test show that the variable teacher competence on teacher performance with work motivation has a significant positive effect, work discipline on teacher performance with work motivation has a negative but insignificant effect.